Perbaikan Lini Produksi untuk Peningkatan Kapasitas pada PT. XYZ - Stefanus Santoso (Jurnal Titra, 2017)
PT. XYZ is a company engaged in the field of shoe industry. One of the production lines of PT XYZ has a target capacity of 180 pairs per hour and the target will be raised to 252 pairs per hour. This increase requires additional operator and also improvement on material procurement. The addition of the required operator on the injection section is 8 operators. The operator in the finishing section requires a total of 34 operators. Improvements that need to be made on the material procurement system from warehouse picking to production line is on the trolley transport system and the addition of 1 operator assistance for warehouse picking. Transportation system initially done every 60 minutes once become every 41 minutes once to archieve 250 pairs target per hour. The problem that exist in the material procurement system is on the procurement of socklining material. There is often a case lack of socklining from the procurement of the material. This problem is analyzed using DMAIC and Fishbone Diagram to determine the root causes. The result of the analysis indicate the occurence of the problem is on the sizing process done in Warehouse Picking. The suggestion given is to oversee the sizing process and provide checksheets to facilitate the process of checking suitability of the amount of material when sizing process done.